Rediscovery of Calymmochilus russoi Gibson, 1995 (Hymenoptera, Chalcidoidea, Eupelmidae), and revision of European Calymmochilus Masi, 1919 - Fusu, Lucian; Askew, Richard R.; Ribes, Antoni (Zootaxa, 2018)
The European species of Calymmochilus Masi (Hymenoptera, Eupelmidae) are revised. Calymmochilus atratus Masi stat. rev. is removed from synonymy under C. subnubilus (Walker) and treated as a valid species. A lectotype is designated for Calymmochilus atratus. The single extant type specimen of Eupelmus subnubilus Walker is considered as lectotype. Calymmochilus bini Fusu sp. n. is described from a single female collected in Sardinia. A female of Calymmochilus russoi Gibson is reported from Spain as a parasitoid in galls of Parapodia sinaica (Frauenfeld) (Lepidoptera, Gelechiidae) on Tamarix (Tamaricaceae), a new national and host record. The species is redescribed and illustrated, this being the first record of the species after its original description. An illustrated key to females and, when known, males of the now six recognized European species of Calymmochilus is given and available biological and distributional data are reviewed.